Conductive ethylene propylene diene rubber and preparation method and application thereof

CN122726580BActive Publication Date: 2026-10-30CHANGSHA CHANGXIAN ELECTRICAL INSULATION MATERIAL CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611216993.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-08-12
Publication Date
2026-10-30
Estimated Expiration
2046-08-12

AI Technical Summary

Technical Problem

泛彩不仅严重影响电缆外观,还会降低屏蔽层与绝缘层或导体之间的界面粘合力,增加界面缺陷,甚至引发局部放电,是电缆行业亟须解决的质量难题

Benefits of technology

本发明通过三元乙丙橡胶、导电炭黑、碳纳米管、离子液体改性剂、硫化剂以及对叔丁基酚醛树脂合理搭配,形成兼具导电网络稳定性、界面相容性和助剂迁移抑制作用的协同体系,在保持材料力学性能和耐永久变形性能的同时,使所得导电三元乙丙橡胶兼具较低的体积电阻率、良好的导电稳定性、抗析出性能、抗泛彩性能和热老化稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122726580B_ABST
    Figure CN122726580B_ABST
Patent Text Reader

Abstract

The application discloses a conductive EPDM (Ethylene Propylene Diene Rubber), a preparation method and application thereof. The conductive EPDM comprises the following raw materials in parts by mass: 100 parts of EPDM, 3-6 parts of an ionic liquid modifier, 3-5 parts of a vulcanizing agent, 2-5 parts of tackifying resin, 55-70 parts of conductive carbon black, and carbon nanotubes. The tackifying resin is p-t-butyl phenol formaldehyde resin. The mass ratio of the conductive carbon black, the carbon nanotubes and the ionic liquid modifier is (10-15):1:(0.8-1.0). The iodine absorption value of the conductive carbon black is greater than or equal to 800 mg / g, and the DBP (Dibutyl Phthalate) absorption value is greater than or equal to 200 mL / 100g. The obtained conductive EPDM has low volume resistivity, good conductive stability, high anti-color bleeding performance, high mechanical performance and permanent deformation resistance, and is suitable for preparing a shielding layer of a cable and a cable accessory.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of conductive rubber technology, and in particular to a conductive EPDM rubber, its preparation method, and its application. Background Technology

[0002] In power cables and cable accessories, conductor shielding and insulation shielding play a crucial role in creating a uniform electric field and preventing partial discharge. These shielding materials are typically composed of a rubber matrix (such as EPDM rubber) and conductive fillers (such as conductive carbon black). EPDM is often used as the matrix material due to its excellent weather resistance, ozone resistance, and electrical insulation properties.

[0003] However, traditional EPDM semiconductive materials typically have high volume resistivity, making it difficult to meet the lower resistivity requirements for shielding materials in ultra-high voltage and high-capacity power transmission. When the volume resistivity is too high, the equipotential performance of the shielding layer deteriorates, easily leading to cable operation failures. To reduce resistivity, existing technologies usually increase the amount of conductive carbon black filling, but this leads to a sharp decline in the material's processing performance (increased Mooney viscosity), reduced mechanical strength, and rough extruded surface. Furthermore, the interface defects caused by high filling amounts may negatively impact the material's electrical stability.

[0004] On the other hand, to improve filler dispersibility or adjust processing performance, various small-molecule additives (such as processing oils, low-molecular-weight components, etc.) are often introduced into the formulation. After the material is vulcanized and molded, especially during long-term storage or under high-temperature conditions, these components easily migrate to the surface of the material, forming blue or colored substances, i.e., "iridescence." Iridescence not only seriously affects the appearance of the cable, but also reduces the interfacial adhesion between the shielding layer and the insulation layer or conductor, increases interfacial defects, and even causes partial discharge, which is a quality problem that the cable industry urgently needs to solve.

[0005] As cable voltage levels gradually increase, how to significantly reduce the volume resistivity of EPDM semiconducting materials, effectively solve the surface discoloration problem, and ensure their performance stability during long-term use while maintaining mechanical properties is a technical challenge that urgently needs to be solved in this field. Summary of the Invention

[0006] The present invention aims to at least solve one of the technical problems existing in the prior art. To this end, the present invention proposes a conductive EPDM rubber.

[0007] The present invention also proposes a method for preparing the conductive EPDM rubber.

[0008] The present invention also proposes the application of the aforementioned conductive EPDM rubber.

[0009] The first aspect of this invention relates to a conductive EPDM rubber, comprising the following raw materials in parts by weight: 100 parts of EPDM rubber 3-6 parts of ionic liquid modifier 3-5 parts of vulcanizing agent 2-5 parts of tackifying resin; 55-70 parts of conductive carbon black Carbon nanotubes; The tackifying resin is p-tert-butylphenolic resin; The mass ratio of the conductive carbon black, carbon nanotubes, and ionic liquid modifier is (10-15):1:(0.8-1.0); the conductive carbon black has an iodine absorption value ≥800mg / g as measured according to GB / T3780.1-2015, and a DBP absorption value ≥200mL / 100g as measured by the instrumental method in GB / T3780.2-2017.

[0010] The conductive EPDM rubber according to the first aspect of the present invention has at least the following beneficial effects: This invention utilizes a rational combination of EPDM rubber, conductive carbon black, carbon nanotubes, ionic liquid modifiers, vulcanizing agents, and p-tert-butylphenolic resin to form a synergistic system that combines conductive network stability, interfacial compatibility, and additive migration inhibition. While maintaining the mechanical properties and resistance to permanent deformation of the material, the resulting conductive EPDM rubber also exhibits low volume resistivity, good conductive stability, anti-exudation properties, anti-coloring properties, and thermal aging stability.

[0011] This invention employs a blend of conductive carbon black with high iodine uptake and DBP absorption values ​​and carbon nanotubes. The high iodine uptake and DBP absorption values ​​of the conductive carbon black increase the contact opportunities between conductive fillers, forming stable conductive contact points. Linear carbon nanotubes act as bridges between the conductive carbon black particles. When blended in a specific ratio, these two materials form a multidimensional conductive network composed of conductive carbon black contact points and carbon nanotube bridging pathways. This improves the utilization efficiency of the conductive filler, reduces the volume resistivity of the material, and enhances the stability of the conductive network under temperature changes and long-term service.

[0012] Ionic liquid modifiers are primarily used to improve the wetting and dispersion of carbon nanotubes. Ionic liquids can interact non-covalently with the surface of carbon nanotubes through π-π interactions, electrostatic interactions, or interfacial adsorption, reducing the tendency for carbon nanotubes to aggregate and allowing them to be more uniformly distributed in the rubber matrix, thus fully utilizing the bridging conductivity of carbon nanotubes. Simultaneously, ionic liquid modifiers help improve the interfacial contact between conductive carbon black, carbon nanotubes, and EPDM rubber, reducing contact resistance and interfacial conduction resistance. This results in a more stable composite structure between the conductive filler system and the rubber matrix, further enhancing the material's conductivity and wide-temperature-range conductivity stability.

[0013] When the proportion of carbon nanotubes is too low, effective bridging cannot be formed; when the proportion is too high, agglomeration is likely to occur, which will reduce the continuity of the conductive network. At the same time, the proportion of ionic liquid modifier needs to be matched with the proportion of carbon nanotubes to ensure the wetting and dispersion of the carbon nanotube surface.

[0014] As a tackifying resin, p-tert-butylphenolic resin possesses both hydrophobic tert-butyl and phenolic hydroxyl structures in its molecular structure. The tert-butyl structure enhances the compatibility between the resin and the non-polar EPDM rubber matrix, allowing it to distribute uniformly within the rubber network. The phenolic hydroxyl structure can form hydrogen bonds, dipole interactions, or adsorptions with active sites on the surface of conductive fillers, strengthening the interfacial bonding between the resin and the filler. Based on these effects, p-tert-butylphenolic resin can improve the interfacial stability between the rubber matrix and the conductive filler, reducing structural degradation caused by component migration and interfacial changes during long-term use, thus maintaining the continuity and stability of the conductive network. Simultaneously, p-tert-butylphenolic resin can improve the stability of the internal component distribution of the system, reduce surface precipitation and coloration, and improve the retention of the rubber network structure under thermal aging conditions.

[0015] Therefore, this invention constructs a composite conductive network by combining conductive carbon black and carbon nanotubes, utilizes ionic liquid modifiers to improve filler dispersion and interfacial conductivity, and combines the stabilizing effect of p-tert-butylphenol resin on the matrix and filler interface, so that the resulting conductive EPDM rubber can maintain a low volume resistivity under different temperature conditions and during long-term thermal aging. At the same time, it has good anti-exudation properties, anti-coloring properties, mechanical properties, resistance to permanent deformation, and thermal aging stability, making it suitable for preparing shielding layers for cables and cable accessories.

[0016] According to some embodiments of the present invention, the EPDM rubber has a Mooney viscosity of ≥55 at ML1+4 / 125℃, an ethylene content of ≥55%, and an ENB content of ≤4.5%. Wherein, the ethylene content and ENB content are mass contents.

[0017] The raw ethylene propylene diene monomer (EPDM) rubber has a relatively high Mooney viscosity, high filling capacity, and can provide appropriate shear force, improving mixing uniformity and mechanical properties. High ethylene content is beneficial for improving mechanical properties. However, higher ENB content may affect heat resistance. Therefore, by controlling the ENB content, ethylene content, and viscosity of EPDM rubber, the rubber material can possess better heat resistance, compression set, and tensile strength, thus obtaining high-performance EPDM rubber.

[0018] According to some embodiments of the present invention, the EPDM rubber has an ENB content of 3.8%-4.5%.

[0019] According to some embodiments of the present invention, the Mooney viscosity of the EPDM rubber at ML1+4 / 125°C is 55-60.

[0020] According to some embodiments of the present invention, the ethylene content of the EPDM rubber is 55%-58%. Controlling the ethylene content within the above range is beneficial for achieving a balance between mechanical properties, processing properties, and low-temperature flexibility.

[0021] According to some embodiments of the present invention, the tensile strength of the EPDM rubber is ≥20MPa, the elongation at break is ≥300%, and the stress at a given elongation (300%) is ≥16MPa.

[0022] According to some embodiments of the present invention, the tackifying resin is 2-4 parts, for example 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts or any value between them.

[0023] According to some embodiments of the present invention, the conductive carbon black is superconducting carbon black. Preferably, the resistivity of the superconducting carbon black is ≤0.2Ω·m.

[0024] According to some embodiments of the present invention, the conductive carbon black has an iodine absorption value of 800-1000 mg / g as measured according to GB / T3780.1-2015, and a DBP absorption value of 200-300 mL / 100g as measured by the instrumental method in GB / T3780.2-2017.

[0025] According to some embodiments of the present invention, the conductive carbon black is 60-70 parts, for example 60 parts, 65 parts, 70 parts or any value between them.

[0026] According to some embodiments of the present invention, the carbon nanotube is a multi-walled carbon nanotube with a diameter of 10-30 nm and a length of 1-30 μm. Preferably, the diameter of the carbon nanotube is 10-20 nm; more preferably, the length of the carbon nanotube is 1-20 μm, more preferably 1-10 μm, and even more preferably 1-5 μm.

[0027] According to some embodiments of the present invention, the mass ratio of the conductive carbon black, carbon nanotubes, and ionic liquid modifier is (12-15):1:(0.8-1.0), for example, 12:1:0.8, 12:1:0.9, 12:1:1, 13:1:0.8, 13:1:0.9, 13:1:1, 14:1:0.8, 14:1:0.9, 14:1:1, 15:1:0.8, 15:1:0.9, 15:1:1, or any ratio therebetween.

[0028] According to some embodiments of the present invention, the ionic liquid modifier is one or more of 1-butyl-3-methylimidazolium hexafluorophosphate and 1-allyl-3-methylimidazolium chloride, and the ionic liquid modifier is used to modify carbon nanotubes to promote the dispersion of carbon nanotubes in EPDM rubber matrix.

[0029] According to some embodiments of the present invention, the ionic liquid modifier is 4-6 parts, for example 4 parts, 5 parts, 6 parts or any value between them.

[0030] According to some embodiments of the present invention, the vulcanizing agent is selected from one or more combinations of dicumyl peroxide, bis-tert-butyldicumyl peroxide, and sulfur.

[0031] According to some embodiments of the present invention, the vulcanizing agent is 3-5 parts, for example 3 parts, 3.5 parts, 4 parts, 4.5 parts, 5 parts or any value between them.

[0032] According to some embodiments of the present invention, the raw materials for preparing the conductive EPDM rubber also include additives.

[0033] According to some embodiments of the present invention, the additive is selected from one or more combinations of plasticizers, antioxidants, activators, dispersants, and vulcanization accelerators.

[0034] According to some embodiments of the present invention, the additive includes a plasticizer, which is selected from one or more combinations of paraffin oil and white oil.

[0035] According to some embodiments of the present invention, the plasticizer is 25-50 parts, specifically 25 parts, 30 parts, 35 parts, 40 parts, 45 parts, 50 parts or any value between them.

[0036] According to some embodiments of the present invention, the additive includes an antioxidant, which is selected from one or more combinations of antioxidant RD, antioxidant MB, antioxidant TMQ, and antioxidant MBZ.

[0037] According to some embodiments of the present invention, the antioxidant is 1-2 parts, specifically 1 part, 1.2 parts, 1.5 parts, 1.8 parts, 2 parts or any value between them.

[0038] According to some embodiments of the present invention, the adjuvant includes an activator selected from one or more combinations of zinc oxide, stearic acid, and zinc stearate.

[0039] According to some embodiments of the present invention, the active agent is 3-6 parts, specifically 3 parts, 4 parts, 5 parts, 6 parts or any value between them.

[0040] According to some embodiments of the present invention, the additive includes a dispersant, which comprises one or more fatty acid derivatives. Preferably, the fatty acid derivative is selected from one or more combinations of fatty acid amides, fatty acid esters, and fatty acid salts. The long-chain hydrocarbon structure in the fatty acid derivative is beneficial to improving the compatibility of the dispersant with the EPDM rubber matrix, and its polar groups are beneficial to improving the wetting and dispersion state of conductive carbon black and carbon nanotubes, thereby reducing the tendency of filler agglomeration, improving the uniformity of mixing and dispersion, and helping to maintain the continuity of the composite conductive network.

[0041] According to some embodiments of the present invention, the dispersant is 3-6 parts, specifically 3 parts, 4 parts, 5 parts, 6 parts or any value between them.

[0042] According to some embodiments of the present invention, the additive includes a vulcanization accelerator selected from one or more combinations of N,N'-dimethyl-N,N'-diphenylthiuram disulfide, N,N-ethylhexane, N-tert-butyl-2-benzothiazole sulfenamide, zinc dialkyl thiophosphate, triallyl isocyanurate, and sulfur. Sulfur can be used alone as a vulcanizing agent or as an auxiliary vulcanizing component when an organic peroxide is used as the vulcanizing agent.

[0043] According to some embodiments of the present invention, the vulcanization accelerator is selected from one or two of zinc dialkyl thiophosphate, triallyl isocyanurate, and sulfur.

[0044] According to some embodiments of the present invention, the vulcanization accelerator is 1-6 parts, specifically 1 part, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts or any value between them.

[0045] According to some embodiments of the present invention, the additives include: 25-50 parts of plasticizer, 1-2 parts of antioxidant, 3-6 parts of activator, 3-6 parts of dispersant, and 1-6 parts of vulcanization accelerator.

[0046] The second aspect of this invention relates to a method for preparing conductive EPDM rubber, comprising: The raw materials, including the EPDM rubber, conductive carbon black, carbon nanotubes, ionic liquid modifier and tackifying resin, are subjected to a first intensive mixing under heating conditions to obtain a compound rubber. After cooling the rubber compound, the raw materials including the vulcanizing agent are added for a second mixing to obtain the conductive EPDM rubber. The raw materials for preparing the first internal mixer may optionally include one or more of activators, antioxidants, dispersants, and plasticizers; the raw materials for preparing the second internal mixer may optionally include vulcanization accelerators.

[0047] The above preparation method is used to prepare the above-mentioned conductive EPDM rubber, and therefore has at least all the beneficial effects of the above-mentioned embodiments of conductive EPDM rubber. The preparation process of this method is simple and easy to produce and apply.

[0048] Mixing is usually carried out using an internal mixer, which is a plasticizing system consisting of two rotors rotating in opposite directions, a mixing chamber, and a top nut. The temperature can be adjusted. In the plasticizing system, the material is subjected to repeated shearing, tearing, stirring, and friction under the pressure of the top nut and the friction of the two rotors rotating in opposite directions, which increases the plasticity of the material and makes it evenly dispersed.

[0049] According to some embodiments of the present invention, the heating temperature is 150-160°C.

[0050] According to some embodiments of the present invention, the first mixing step includes: performing a first mixing step on the EPDM rubber at 150-160°C, adding the preparation raw materials including the tackifying resin for a second mixing step, and adding the preparation raw materials including the conductive carbon black, carbon nanotubes, and ionic liquid modifier for a third mixing step.

[0051] According to some embodiments of the present invention, when the raw materials for preparing the conductive EPDM rubber further include the activator and / or the antioxidant and / or the dispersant, the second mixing step further includes adding the activator and / or the antioxidant and / or the dispersant for a second mixing step.

[0052] According to some embodiments of the present invention, the mixing time of the first step is 1-2 minutes.

[0053] According to some embodiments of the present invention, the second step of mixing takes 4-6 minutes.

[0054] According to some embodiments of the present invention, when the raw materials for preparing the conductive EPDM rubber also include the plasticizer, the third step of mixing is: adding the raw materials for preparing the conductive carbon black, carbon nanotubes, ionic liquid modifier and plasticizer to perform the third step of mixing.

[0055] According to some embodiments of the present invention, the third step of mixing is either a one-step mixing or a multi-step mixing. Multi-step mixing refers to adding the corresponding raw materials in stages and mixing them in stages. The staged addition can be divided into two or more stages, with the amount of material added in each stage being the same or different, and the composition of the raw materials added in each stage being the same or different.

[0056] According to some embodiments of the present invention, the total time for the third mixing step is 5-10 minutes.

[0057] According to some embodiments of the present invention, the temperature of the second mixing is 50-70°C.

[0058] According to some embodiments of the present invention, the second mixing time is 2-5 minutes.

[0059] According to some embodiments of the present invention, after cooling and before the second internal mixing, the mixture further includes: pre-mixing the compound obtained from the first internal mixing.

[0060] According to some embodiments of the present invention, the premixing temperature is 50-70°C.

[0061] According to some embodiments of the present invention, the premixing time is 1-2 minutes.

[0062] The third aspect of the present invention relates to the application of the above-mentioned conductive EPDM rubber in the preparation of shielding layers for cables and / or cable accessories.

[0063] Given the advantages of conductive EPDM rubber mentioned above, it is possible to improve the performance and service life of cables and cable accessories using conductive EPDM rubber.

[0064] In this document, unless otherwise stated, "parts" refers to parts by weight; with EPDM rubber as 100 parts by weight, the amounts of other raw materials are all relative to 100 parts by weight of EPDM rubber. For example, 2-4 parts of tackifying resin means that the amount of tackifying resin is 2-4 parts by weight relative to 100 parts by weight of EPDM rubber.

[0065] "Multiple" means two or more, and "above" includes the number itself; when it comes to a numerical range, it includes the endpoint and any subset within that range.

[0066] "Room temperature" refers to 23±2℃.

[0067] Additional aspects and advantages of the invention will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of the invention. Attached Figure Description

[0068] Figure 1 This is a photograph of the sample of Example 1 of the present invention after being processed under appearance test conditions.

[0069] Figure 2 This is a photograph of the sample of Comparative Example 2 of the present invention after being processed under appearance test conditions.

[0070] Figure 3 This is a photograph of the sample of Comparative Example 3 of the present invention after being processed under appearance test conditions.

[0071] Figure 4 This is a photograph of the sample of Comparative Example 4 of the present invention after being processed under appearance test conditions. Detailed Implementation

[0072] The embodiments of the present invention are described in detail below. These embodiments are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention.

[0073] In the following embodiments, the relevant raw materials are described as follows: EPDM rubber: Shaanxi Yanchang Petroleum Yan'an Energy and Chemical Co., Ltd., EPDM-Y-05H4D4 EPDM rubber, Mooney viscosity ML (1+4, 125℃) is 59.4, ethylene content is 57.82%, ENB content is 4.07%, tensile strength is 21.5MPa, elongation at break is 362%, and tensile stress at a given elongation (300%) is 16.8MPa.

[0074] Conductive carbon black: Tianjin Yiborui Chemical Co., Ltd., superconducting carbon black F200A, iodine absorption value 800-900mg / g, DBP absorption value 230-280mL / 100g, resistivity ≤0.2Ω·m; Weifang Bola Carbon Materials Co., Ltd., conductive carbon black BCD7145, iodine absorption value 90mg / g, DBP absorption value 150mL / 100g.

[0075] Tackifying resin: Jiangsu Ruiba New Material Technology Co., Ltd., RN-1440, thermoplastic p-tert-butylphenol formaldehyde resin.

[0076] Dispersant: Jiangsu Ruiba New Material Technology Co., Ltd., RL-20, a mixture of fatty acid esters and fatty acid salts.

[0077] Carbon nanotubes: Beijing Deco Island Gold Technology Co., Ltd., multi-walled carbon nanotubes CNT404, with a diameter of 10-20 nm, a length of 1-2 μm, a purity of ≥98%, and a specific surface area of ​​≥200 m².2 / g, conductivity EC≥150s / cm.

[0078] Ionic liquid modifier: 1-Butyl-3-methylimidazolium hexafluorophosphate, purity ≥99%, pH 7-8.

[0079] Internal mixer: LN-LT-1L type internal mixer manufactured by Guangdong Lina Industrial Co., Ltd.

[0080] Unless otherwise specified, all other raw materials or equipment involved are commercially available and readily available.

[0081] Example 1 This embodiment prepares a conductive EPDM rubber, comprising the following raw materials: 100 kg EPDM rubber (EPDM-Y-05H4D4), 60 kg superconducting carbon black (F200A), 5 kg multi-walled carbon nanotubes (CNT404), 4 kg ionic liquid modifier, 40 kg paraffin oil, 1.5 kg antioxidant MBZ, 4 kg zinc oxide (purity above 95.5 wt%), 2.5 kg tackifying resin (RN-1440), 4 kg rubber processing dispersant (RL-20), 3.5 kg vulcanizing agent DCP, 1.2 kg rubber vulcanization accelerator (TAIC, triallyl isocyanurate), and 0.2 kg sulfur.

[0082] The preparation steps are as follows: (1) Heat the internal mixer to 150-160℃ and put in 100kg of EPDM rubber for 1min; (2) Add 4kg zinc oxide, 1.5kg antioxidant MBZ, 2.5kg tackifying resin and 4kg rubber processing dispersant and mix for 4 minutes. After mixing evenly, proceed to the following steps; (3) Add 15kg of paraffin oil, 30kg of superconducting carbon black, 2.5kg of multi-walled carbon nanotubes and 2kg of ionic liquid modifier and mix for 3 minutes. After mixing evenly, proceed to the following steps. (4) Add 25kg of paraffin oil, 30kg of superconducting carbon black, 2.5kg of multi-walled carbon nanotubes and 2kg of ionic liquid modifier and mix for 3 minutes. After mixing evenly, proceed to the following steps. (5) After mixing evenly, remove the mixed rubber block from the internal mixer; (6) Cool the internal mixer to 50-70℃, and put the prepared compound into the internal mixer and mix for 1 minute; (7) Add 3.5 kg of vulcanizing agent DCP, 1.2 kg of rubber vulcanization accelerator TAIC, and 0.2 kg of sulfur and mix for 3 min; (8) After the mixture is evenly mixed, the mixed rubber block is taken out from the internal mixer to obtain conductive EPDM rubber.

[0083] Example 2 This embodiment prepares a conductive EPDM rubber, comprising the following raw materials: 100 kg EPDM rubber (EPDM-Y-05H4D4), 70 kg superconducting carbon black (F200A), 5 kg multi-walled carbon nanotubes (CNT404), 5 kg ionic liquid modifier, 40 kg paraffin oil, 1.5 kg antioxidant MBZ, 4 kg zinc oxide (purity above 95.5 wt%), 2.5 kg tackifying resin (RN-1440), 4 kg rubber processing dispersant (RL-20), 3.5 kg vulcanizing agent DCP, 1.2 kg rubber vulcanization accelerator (TAIC, triallyl isocyanurate), and 0.2 kg sulfur.

[0084] The preparation steps are as follows: (1) Heat the internal mixer to 150-160℃ and put in 100kg of EPDM rubber for 1min; (2) Add 4kg zinc oxide, 1.5kg antioxidant MBZ, 2.5kg tackifying resin and 4kg rubber processing dispersant and mix for 4 minutes. After mixing evenly, proceed to the following steps; (3) Add 15kg of paraffin oil, 35kg of superconducting carbon black, 2.5kg of multi-walled carbon nanotubes and 2.5kg of ionic liquid modifier and mix for 3 minutes. After mixing evenly, proceed to the following steps. (4) Add 25kg of paraffin oil, 35kg of superconducting carbon black, 2.5kg of multi-walled carbon nanotubes, and 2.5kg of ionic liquid modifier and mix for 3 minutes. After mixing evenly, proceed to the following steps. (5) After mixing evenly, remove the mixed rubber block from the internal mixer; (6) Cool the internal mixer to 50-70℃, and put the prepared compound into the internal mixer and mix for 1 minute; (7) Add 3.5 kg of vulcanizing agent DCP, 1.2 kg of rubber vulcanization accelerator TAIC, and 0.2 kg of sulfur and mix for 3 min; (8) After the mixture is evenly mixed, the mixed rubber block is taken out from the internal mixer to obtain conductive EPDM rubber.

[0085] Comparative Example 1 This comparative example prepared a conductive EPDM rubber, comprising the following raw materials: 100 kg EPDM rubber (EPDM-Y-05H4D4), 60 kg superconducting carbon black (F200A), 5 kg multi-walled carbon nanotubes (CNT404), 2 kg ionic liquid modifier, 40 kg paraffin oil, 1.5 kg antioxidant MBZ, 4 kg zinc oxide (purity above 95.5 wt%), 2.5 kg tackifying resin (RN-1440), 4 kg rubber processing dispersant (RL-20), 3.5 kg vulcanizing agent DCP, 1.2 kg rubber vulcanization accelerator (TAIC, triallyl isocyanurate), and 0.2 kg sulfur.

[0086] The preparation steps are as follows: (1) Heat the internal mixer to 150-160℃ and put in 100kg of EPDM rubber for 1min; (2) Add 4kg zinc oxide, 1.5kg antioxidant MBZ, 2.5kg tackifying resin and 4kg rubber processing dispersant and mix for 4 minutes. After mixing evenly, proceed to the following steps; (3) Add 15kg of paraffin oil, 30kg of superconducting carbon black, 2.5kg of multi-walled carbon nanotubes and 1kg of ionic liquid modifier and mix for 3 minutes. After mixing evenly, proceed to the following steps. (4) Add 25kg of paraffin oil, 30kg of superconducting carbon black, 2.5kg of multi-walled carbon nanotubes (CNT404), and 1kg of ionic liquid modifier and mix for 3 minutes. After mixing evenly, proceed to the following steps. (5) After mixing evenly, remove the mixed rubber block from the internal mixer; (6) Cool the internal mixer to 50-70℃, and put the prepared compound into the internal mixer and mix for 1 minute; (7) Add 3.5 kg of vulcanizing agent DCP, 1.2 kg of rubber vulcanization accelerator TAIC, and 0.2 kg of sulfur and mix for 3 min; (8) After the mixture is evenly mixed, the mixed rubber block is taken out from the internal mixer to obtain conductive EPDM rubber.

[0087] Comparative Examples 2-5 Conductive EPDM rubber was prepared in Comparative Examples 2-5, and the preparation method was the same as in Example 1. The difference from Example 1 is that the raw material composition of each comparative example is shown in Table 1, and the raw materials and amounts listed in Table 1 were fed in accordance with the specifications. Unless otherwise specified, the order of feeding and process conditions were the same as in Example 1.

[0088] Comparative Example 6 This comparative example prepared a conductive EPDM rubber, comprising the following raw materials: 100 kg EPDM rubber (EPDM-Y-05H4D4), 50 kg superconducting carbon black (F200A), 6 kg multi-walled carbon nanotubes (CNT404), 4 kg ionic liquid modifier, 40 kg paraffin oil, 1.5 kg antioxidant MBZ, 4 kg zinc oxide (purity above 95.5 wt%), 2.5 kg tackifying resin (RN-1440), 4 kg rubber processing dispersant (RL-20), 3.5 kg vulcanizing agent DCP, 1.2 kg rubber vulcanization accelerator (TAIC, triallyl isocyanurate), and 0.2 kg sulfur.

[0089] The preparation steps are as follows: (1) Heat the internal mixer to 150-160℃ and put in 100kg of EPDM rubber for 1min; (2) Add 4kg zinc oxide, 1.5kg antioxidant MBZ, 2.5kg tackifying resin, and 4kg rubber processing dispersant and mix for 4 minutes. After mixing evenly, proceed to the following steps. (3) Add 15kg of paraffin oil, 25kg of superconducting carbon black, 3kg of multi-walled carbon nanotubes, and 2kg of ionic liquid modifier and mix for 3 minutes. After mixing evenly, proceed to the following steps. (4) Add 25kg of paraffin oil, 25kg of superconducting carbon black, 3kg of multi-walled carbon nanotubes, and 2kg of ionic liquid modifier and mix for 3 minutes. After mixing evenly, proceed to the following steps. (5) After mixing evenly, remove the mixed rubber block from the internal mixer; (6) Cool the internal mixer to 50-70℃, and put the prepared compound into the internal mixer and mix for 1 minute; (7) Add 3.5 kg of vulcanizing agent DCP, 1.2 kg of rubber vulcanization accelerator TAIC, and 0.2 kg of sulfur and mix for 3 min; (8) After the mixture is evenly mixed, the mixed rubber block is taken out from the internal mixer to obtain conductive EPDM rubber.

[0090] Table 1

[0091] Test case Each sample to be tested was vulcanized at 165℃ for 30 minutes to obtain the corresponding test specimen.

[0092] Tear strength was determined according to GB / T 529-2008, using method B with a right-angled specimen.

[0093] Tensile strength and elongation at break were determined in accordance with GB / T 528-2009, using type 1 dumbbell-shaped specimens.

[0094] The test methods for the rate of change of tensile strength and the rate of change of elongation at break are as follows: The sample is aged at 150℃ for 720 hours. After being removed and restored to room temperature, the tensile strength and elongation at break after aging are measured under the same conditions as described above, and the corresponding rate of change of performance is calculated. The rate of change of performance is calculated using the following formula: Rate of change of performance (%) = (Performance value after aging - Performance value before aging) / Performance value before aging × 100%.

[0095] Volume resistivity was determined according to GB / T 3048.3-2007. The sample dimensions were 110mm (length) × 50mm (width) × 2mm (thickness). The testing instrument was a BD400H semi-conductive rubber and plastic material resistivity tester, purchased from Xi'an Honghu Testing Instruments Co., Ltd. Before testing, the sample was placed at the corresponding test temperature for 24 hours, and then the volume resistivity was measured at that test temperature; the test temperatures were -40℃, 23℃, and 90℃.

[0096] Volume resistivity after aging: The sample was aged in an environment of 150℃ for 7 days (168h), and then placed at room temperature (test temperature) for 24h. The volume resistivity after aging was then measured according to the volume resistivity test method described above.

[0097] Appearance: Place the material in a constant temperature and humidity chamber at 70℃ and 95% relative humidity for 720 hours. After removal, visually inspect the surface of the material for obvious iridescence or exudates.

[0098] Compression set was determined according to GB / T 7759.1-2015, using type A specimens, a compression ratio of 25%, a test temperature of 100℃, and a test time of 168h.

[0099] Tensile permanent deformation was determined according to Appendix B of T / CEC 118-2016. The specimens used were Type 1 dumbbell-shaped specimens as specified in GB / T 528-2009, with an initial gauge length of 25 mm. During the test, the specimens were stretched to 200% of their original gauge length and held at 90°C for 168 hours. The recovery time after releasing the tension was 24 hours.

[0100] The test results are shown in Table 2.

[0101] Table 2

[0102] It can be seen that the conductive EPDM rubbers obtained in Examples 1-2 all exhibit good appearance stability and mechanical properties. After being placed at 70℃ and 95% relative humidity for 720 hours, no precipitation or discoloration occurred. Their tensile strength, elongation at break, tear strength, compression set, tensile set, and after heat aging, the volume resistivity, rate of change of tensile strength, and rate of change of elongation at break all meet the technical requirements. The above results indicate that the present invention, using a combination of composite conductive fillers, ionic liquid modifiers, and tackifying resins, can improve the appearance stability and conductivity of the material while maintaining the mechanical properties and aging resistance of the rubber.

[0103] Compared with Example 1, the amount of ionic liquid modifier in Comparative Example 1 was insufficient, making it difficult to fully improve the wetting and dispersion state of carbon nanotubes in the EPDM rubber matrix. The carbon nanotubes could not fully exert their bridging effect on the conductive carbon black particles, resulting in a decrease in the continuity and stability of the composite conductive network.

[0104] Comparative Example 2, without the addition of tackifying resin, showed severe precipitation and obvious iridescence after constant temperature and humidity treatment, and its elongation at break changed significantly. This indicates that without the addition of tackifying resin, some low molecular weight components in the formulation are more likely to migrate to the material surface or accumulate during hot and humid environments or thermal aging, resulting in surface precipitation, iridescence, and a decrease in elongation retention after aging.

[0105] Comparative Examples 3 and 4 used petroleum resin C9 and terpene resin T100, respectively, to replace the p-tert-butylphenol resin in Example 1. Both petroleum resin C9 and terpene resin T100 are hydrocarbon resins, lacking polar interaction sites such as phenolic hydroxyl groups in their molecular structure. This makes it difficult to enhance the interfacial bonding between the resin and conductive carbon black, reducing the inhibition of migration and precipitation of low-molecular-weight components.

[0106] Migratory components in rubber systems may originate from migratory substances adsorbed by conductive fillers and additives such as plasticizers. The migration behavior of these components may be influenced by factors such as their molecular weight, molecular structure, compatibility with the rubber matrix, rubber crosslinking network structure, and filler interfacial state. Components with lower molecular weights or weaker compatibility with the rubber matrix may gradually migrate to and accumulate on the material surface under long-term heat and humidity or heat aging conditions, potentially leading to iridescence on the material surface.

[0107] In contrast, Example 1 uses p-tert-butylphenolic resin containing polar functional groups such as phenolic hydroxyl groups, which can form hydrogen bonds or dipole interactions with oxygen-containing functional groups on the surface of conductive carbon black, thereby improving the interfacial bonding strength between the resin and the filler. Simultaneously, the phenolic resin has a high rigidity structure and a large molecular size, which can increase the diffusion resistance of low-molecular-weight substances in the rubber network, thereby reducing the migration rate of plasticizers and residual small carbon black molecules and decreasing their precipitation onto the material surface. Furthermore, a stable resin-filler interface is beneficial for maintaining the dispersion state of the conductive carbon black, preserving the stability of the conductive network under low-temperature conditions, and improving the elongation properties after thermal aging.

[0108] Figures 1-4 The images shown are, in order, photographs of samples from Examples 1, 2, 3, and 4 of this invention after being processed under appearance testing conditions, corresponding to the appearance states of "no precipitation, no iridescence," "severe precipitation, obvious iridescence," "obvious precipitation, iridescence," and "slight precipitation, iridescence," respectively. During long-term storage or thermal aging of conductive EPDM rubber, if the system's ability to fix internal low-molecular-weight components is insufficient, some small molecules will gradually migrate to and accumulate on the material surface. When these migrants form a continuous or locally enriched layer on the material surface, they alter the surface's optical properties, resulting in thin-film interference and a change in surface color, i.e., iridescence. The higher the degree of precipitation, the more obvious the migration layer formed on the surface, with the appearance showing a trend of gradual development from slight shine and localized iridescence to a distinct colored film layer and even grayish-white precipitation.

[0109] Comparative Example 5 replaced superconducting carbon black F200A with conductive carbon black BCD7145. Compared with Example 1, the tensile strength and tear strength of Comparative Example 5 decreased, while the compression set and tensile set increased to 9.01% and 12.47%, respectively, both failing to meet the requirements. Its volume resistivity increased significantly at all test temperatures, and also increased significantly after aging. Simultaneously, Comparative Example 5 exhibited severe precipitation and obvious iridescence, with a change in elongation at break of -29.92%. These results indicate that, under the formulation system and test conditions of this application, using conductive carbon black with low iodine uptake and DBP absorption values ​​is not conducive to obtaining a continuous and stable composite conductive network and may reduce the adsorption and binding effect of conductive fillers on some low-molecular-weight components, thereby decreasing the material's conductivity, appearance stability, and resistance to permanent deformation.

[0110] Compared to Examples 1 and 2, Comparative Example 6 exhibits lower conductivity. As the proportion of carbon nanotubes in the conductive filler increases, the probability of contact, entanglement, and aggregation between carbon nanotubes correspondingly increases. Simultaneously, the decrease in the mass ratio of the ionic liquid modifier to carbon nanotubes weakens its wetting and dispersing effect on the carbon nanotubes, easily leading to carbon nanotube aggregation, which is detrimental to the construction of conductive pathways. Furthermore, the decrease in the proportion of conductive carbon black ultimately results in a significant reduction in the material's conductivity.

[0111] In summary, through the synergistic effect of its components, the present invention enables the obtained conductive EPDM rubber to possess low volume resistivity, good mechanical properties, small permanent deformation, thermal aging stability, and anti-coloring properties, making it suitable for use in the preparation of shielding layers for cables and cable accessories.

[0112] The present invention has been described in detail above with reference to the embodiments. However, the present invention is not limited to the above embodiments. Within the scope of knowledge possessed by those skilled in the art, various changes can be made without departing from the spirit of the present invention.

Claims

1. A conductive EPDM rubber, characterized in that, The following raw materials are included in the preparation by weight: 100 parts of EPDM rubber 3-6 parts of ionic liquid modifier 3-5 parts of vulcanizing agent 2-5 parts of tackifying resin, 55-70 parts of conductive carbon black Carbon nanotubes; The tackifying resin is thermoplastic p-tert-butylphenol formaldehyde resin; the ionic liquid modifier is 1-butyl-3-methylimidazolium hexafluorophosphate. The mass ratio of the conductive carbon black, carbon nanotubes, and ionic liquid modifier is (10-15):1:(0.8-1.0); the conductive carbon black is superconducting carbon black, the resistivity of the conductive carbon black is ≤0.2Ω·m, the iodine absorption value of the conductive carbon black measured according to GB / T3780.1-2015 is ≥800mg / g, and the DBP absorption value measured according to the instrumental method in GB / T3780.2-2017 is ≥200mL / 100g.

2. The conductive EPDM rubber according to claim 1, characterized in that, The carbon nanotubes are multi-walled carbon nanotubes with a diameter of 10-30 nm and a length of 1-30 μm; and / or, the conductive carbon black has an iodine absorption value of 800-1000 mg / g as measured according to GB / T3780.1-2015, and a DBP absorption value of 200-300 mL / 100 g as measured by the instrumental method in GB / T3780.2-2017.

3. The conductive EPDM rubber according to claim 1, characterized in that, The conductive carbon black is 60-70 parts by weight; and / or the mass ratio of the conductive carbon black, carbon nanotubes, and ionic liquid modifier is (12-15):1:(0.8-1.0).

4. The conductive EPDM rubber according to claim 1, characterized in that, The ionic liquid modifier is present in 4-6 parts by weight.

5. The conductive EPDM rubber according to claim 1, characterized in that, The EPDM rubber has a Mooney viscosity of ≥55 at ML1+4 / 125℃, an ethylene content of ≥55%, and an ENB content of ≤4.5%; and / or, the tackifying resin is 2-4 parts by weight.

6. The conductive EPDM rubber according to claim 1, characterized in that, The vulcanizing agent is selected from one or more combinations of dicumyl peroxide, di-tert-butyl peroxide, and sulfur; and / or, the vulcanizing agent is 3-5 parts by weight.

7. The conductive EPDM rubber according to claim 1, characterized in that, The raw materials for preparing the conductive EPDM rubber also include additives, which are selected from one or more combinations of plasticizers, antioxidants, activators, dispersants, and vulcanization accelerators.

8. The conductive EPDM rubber according to claim 7, characterized in that, The plasticizer is selected from one or more combinations of paraffin oil and white oil; and / or, the plasticizer is 25-50 parts by weight; and / or, the antioxidant is selected from one or more combinations of antioxidant RD, antioxidant MB, antioxidant TMQ, and antioxidant MBZ; and / or, the antioxidant is 1-2 parts by weight; and / or, the activator is selected from one or more combinations of zinc oxide, stearic acid, and zinc stearate; and / or, the activator is 3-6 parts by weight; and / or, the The dispersant is selected from one or more of fatty acid amides, fatty acid esters, and fatty acid salts; and / or, the dispersant is 3-6 parts by weight; and / or, the vulcanization accelerator is selected from one or more of N,N'-dimethyl-N,N'-diphenylthiuram disulfide, N,N-ethylidene thiourea, N-tert-butyl-2-benzothiazole sulfenamide, zinc dialkyl thiophosphate, triallyl isocyanurate, and sulfur; and / or, the vulcanization accelerator is 1-6 parts by weight.

9. The method for preparing conductive EPDM rubber according to any one of claims 1-8, characterized in that, include: The raw materials, including the EPDM rubber, conductive carbon black, carbon nanotubes, ionic liquid modifier and tackifying resin, are subjected to a first intensive mixing under heating conditions to obtain a compound rubber. After cooling the rubber compound, the raw materials including the vulcanizing agent are added for a second mixing to obtain the conductive EPDM rubber. The raw materials for preparing the first internal mixer may optionally include one or more of activators, antioxidants, dispersants, and plasticizers; the raw materials for preparing the second internal mixer may optionally include vulcanization accelerators.

10. The use of the conductive EPDM rubber as described in any one of claims 1-8 in the preparation of shielding layers for cables and / or cable accessories.

Citation Information

Patent Citations

  • Research and development of ionic liquid carbon nano far-infrared radiation heating material and application thereof

    CN106183320A

  • Conductive ethylene propylene diene monomer and preparation method and application thereof

    CN118834473A